Current status of interventional endoscopic ultrasound. Issue 5 (24th April 2017) - Ryozawa, Shomei; Fujita, Naotaka; Irisawa, Atsushi; Hirooka, Yoshiki; Mine, Tetsuya
Abstract : Endoscopic ultrasound (EUS) is being used increasingly in the management of pancreatic fluid collection, biliary and pancreatic duct drainage in cases of failed endoscopic retrograde cholangiopancreatography, drainage of the gallbladder, and other conditions. The role of interventional EUS is rapidly expanding and new interventions are continuously emerging. The development of devices could be a major breakthrough in the field of interventional EUS. New devices would enable the expansion of its role even further and prompt its widespread use in clinical practice. This review focuses on the current status of interventional EUS, especially highlighting the topics that are presently drawing the interest of endoscopists.